Challenges faced in funding Business Education in Nigeria Educational Sector - Eshemogie, Kasimu Osigbeme; Owie, T. Y. (NIU Journal of Social Sciences; Vol 9 No 1 (2023): NIU Journal of Social Sciences, Vol. 9 No. 1, March 2023, 2023)
Abstract . This paper attempted to review the challenges faced in funding business education in Nigeria educational sector. Business education in particular aims at equipping its recipients with practical skills and values to become self-reliant and employable in the world of work. The main purpose of education is to equip individual with knowledge, skill, attitude and values desirable in the society. The discusses the relevant conceptual analysis which covers challenges faced with underfunding business education, Lack of Training and Re-Training of Business Education Teachers, Inadequate Facilities, Lack of Functional Equipment, Obsolete Machines and Poor Laboratories, the effect of adequate funding of business education and the roles of educational stakeholders in funding education in Nigeria, which includes. The paper recommends that Government should sensitize educational managers how to manage the hard earned resources allocated to education, Workshops and orientations should be organized by the official in the Ministry of Education, National Universities Commission to manage the funds allocated to education and home to implement the funds as they prepare their budgets, Government and other educational stakeholders should be creative by generating another source of revenue for funding education and that Government should sensitize parents, Civil Society Organization, Non-Governmental Agencies and other stakeholders that funding education is a responsibility of all. Keywords: Business Education, Funding, Nigeria Educational Sector, Stakeholders.